IMPLEMENTING ACI KEBURAN AS A FORM OF CULTURAL ATTRACTION IN STRENGTHENING THE LOCAL ECONOMY IN THE TIME OF COVID-19 BASED ON REGIONAL REGULATION OF THE PROVINCIAL GOVERNMENT OF BALI YEAR 2019 IN KELUSA VILLAGE - Putri Wirantari, I Dewa Ayu (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2023)
Abstract strengthening of the local economy by the Bali Provincial Government can be synergized through the Bali Provincial Regulation Number 1 of 2019 concerning the Implementation of Cultural Attractions. Where in this regional regulation is regulated regarding the implementation of cultural attractions which are expected to be able to protect culture and traditions but can strengthen the local economy, so that escape can strengthen the local economy in the province of Bali through the economic cycle contained in chicken grafting shows. It can be seen that the many components of the community involved in its implementation are able to gain economic benefits. Tracing the implementation of the escape through the Bali provincial regulation number 1 of 2019 as an effort to strengthen the local economy during the COVID-19 pandemic can be reviewed in Kelusa village, Payangan sub-district, Gianyar Regency. Which can be seen that the implementation of this burial tradition is still carried out in such a way during the covid-19 pandemic. The purpose of this study is to analyze and describe the strengthening of the local economy in the Implementation of Aci Keburan in Kelusa Village During the Covid-19 Period Based on the 2019 Bali Provincial Government Regulation. The research method uses descriptive qualitative research methods, qualitative descriptive research which is intended as a measurement of social phenomena. certain people who are able to develop concepts and collect facts but do not carry out hypotheses